pH-dependent Osteoimmunomodulation: Molecular mechanisms and therapeutic targeting in bone disorders - Chuanlong Wu; Zujun Sun; Chuan He; Ruixin Sun (Pharmacological Research)
The bone microenvironment represents a highly sophisticated ecosystem comprising diverse cellular components—including osteoblasts, osteoclasts, immune cells, endothelial cells, and mesenchymal stem cells—that interact dynamically to maintain skeletal homeostasis and facilitate repair. Emerging insights from osteoimmunology have revealed that acid-base balance serves as a central regulatory node in bone remodeling, working synergistically with other physiological signals to fine-tune osteoclast/osteoblast activity through intricate molecular crosstalk. Notably, even subtle pH fluctuations within this microenvironment can exert profound effects on both bone and immune cell function. This review provides a comprehensive examination of: (1) the physiological principles governing acid-base balance in bone, (2) the pathological consequences of its dysregulation on bone remodeling via osteoimmune networks, and (3) the therapeutic promise of pH-modulating strategies for bone disorders such as osteoporosis and osteoarthritis. Our synthesis positions bone as a precision acid-base regulatory organ while establishing a mechanistic framework for developing targeted therapies that restore pH equilibrium in skeletal tissues.